PRESENTATION OF CONGESTIVE CARDIAC FAILURE IN CHILDREN WITH VENTRICULAR SEPTAL DEFECT - Hussain, Maqbool; Hussain, Sajjad; Krishin, Jai; Abbasi, Saleem (Journal of Ayub Medical College Abbottabad, 2010)
Background: While there is much data on cardiac problems of adults, there is a limited statistical data available to evaluate the magnitude of the cardiac problems in children in Pakistan. Many of these children present with recurrent chest infections and congestive cardiac failure (CCF), and are managed by general practitioners. A careful search for underlying cardiac problems and awareness about the presentation of CCF and its magnitude will definitely decrease the morbidity and mortality of these children. The objective of this study was to see the frequency and clinical presentation of CCF in children with Ventricular Septal Defect (VSD). Methods: Forty-nine patients met the preset criteria during the study period of 6 months. A detailed history and physical examination with special emphasis on symptoms and signs was sought and the findings were noted in a questionnaire. Data was analysed using SPSS-11. Frequencies and percentages were calculated for all categorical variables. Results: CCF in VSD was found more in males, with a male to female ratio of 1.45:1. Majority (63.1%) of the patients presented in infancy. The common symptoms at presentation were dyspnoea (98%), cough (83.7%), and feeding difficulty (9.6%). Other important symptoms were fever, fatigue, failure to thrive, sweating and wheezing. The common physical signs in order of frequency were murmur 98%, tachypnoea 91.8%, tachycardia 89.8%, hepatomegally 89.9% and crackles in chest 85.7%. Other presenting signs were displaced apex beat 57%, oedema 28.6% and chest deformity 20.4%. Regarding the type of VSD, perimembranous was the commonest 61.2% as confirmed by echocardiography. Conclusion: This study was done on a smaller scale in hospitalised children. The exact studies regarding CCF in paediatric patients are scarce. There is a need to design more studies in children with CCF. Early recognition of signs and symptoms of CCF on paediatric patients with VSD and awareness at primary health care level can prevent the delay in the diagnosis and early referrals by GPs to hospital setup will definitely reduce the morbidity and mortality. Keywords: Children, Congestive cardiac failure, Ventricular septal defect